Kajian Pengaruh Residu Kompos Biochar Dan Aplikasi Teh Kompos terhadap Pembentukkan Bawang Putih (Allium sativum L. ) Siung Tunggal Menggunakan Bibit Asal Bagian Luar Siung Majemuk pada Penanaman Tahun Kedua - Eduardus Yosef Neonbeni; Adriana Hoar (Savana Cendana, 2020)
The aim of the study was to determine the effect of biochar compost residue on the second year of planting and the proper application of compost tea on the formation of single clove garlic (Allium sativum L.) using seeds from the outside of compound cloves. The research was carried out from June to September 2019, in the experimental garden of the Faculty of Agriculture, University of Timor, Sasi Village, Kefamenanu City District, North Central Timor Regency. Using a factorial randomized block design (RAK) 3 x 3. The first factor was the residue of biochar compost that was applied one year earlier, which consisted of 3 levels, namely without biochar compost, 10% compost plus biochar, 20% biochar plus compost. The second factor was the application of compost tea which consisted of 3 levels, namely, without compost tea, pure compost tea, compost with added biochar, which was repeated 3 times plus control so that there were 30 experimental plot units. The results showed that there was an interaction between the combination of 10% biochar compost residue treatment and the application of pure compost tea on the soil moisture content of 45 DAP, and the number of tubers per plot. Although there was no interaction between treatment of pure compost residue and pure compost tea, the weight of single clove tuber per plot was 0.93 t/ha. The main effect of 10% biochar compost residue treatment was to increase the yield of total tuber weight, single clove bulb weight, and compound clove bulb weight although not significantly different. The main effect of the application of biochar compost tea treatment was to increase the total tuber weight yield, single clove bulb weight, while the compound tuber weight yield was higher when applying pure compost tea.